2010
DOI: 10.1007/s11682-009-9084-1
|View full text |Cite
|
Sign up to set email alerts
|

Concordance and Discordance Between Brain Perfusion and Atrophy in Frontotemporal Dementia

Abstract: The aim of this study was to determine if a dissociation between reduced cerebral perfusion and gray matter (GM) atrophy exists in frontotemporal dementia (FTD). The study included 28 patients with FTD and 29 cognitive normal (CN) subjects. All subjects had MRI at 1.5 T, including T1-weighted structural and arterial spin labeling (ASL) perfusion imaging. Non-parametric concordance/discordance tests revealed that GM atrophy without hypoperfusion occurs in the premotor cortex in FTD whereas concordant GM atrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 35 publications
6
48
1
1
Order By: Relevance
“…While much of our findings resemble SPECT-based observations in dementia (Matsuda et al, 2002; Matsuda et al, 2003) and more recently using CASL (Dai et al, 2009; Hayasaka et al, 2006; Nagata et al, 2000; Schuff et al, 2009; Shimizu et al, 2010; Yang et al, 2002) and AD (Tosun et al, 2010), some exceptions were found, such as in the amygdala (Dai et al, 2009) and hippocampus (Alsop et al, 2008; Dai et al, 2009; Fleisher et al, 2009; Heo et al, 2010; Ito et al, 2006; Nagata et al, 2000). …”
Section: Discussionsupporting
confidence: 88%
“…While much of our findings resemble SPECT-based observations in dementia (Matsuda et al, 2002; Matsuda et al, 2003) and more recently using CASL (Dai et al, 2009; Hayasaka et al, 2006; Nagata et al, 2000; Schuff et al, 2009; Shimizu et al, 2010; Yang et al, 2002) and AD (Tosun et al, 2010), some exceptions were found, such as in the amygdala (Dai et al, 2009) and hippocampus (Alsop et al, 2008; Dai et al, 2009; Fleisher et al, 2009; Heo et al, 2010; Ito et al, 2006; Nagata et al, 2000). …”
Section: Discussionsupporting
confidence: 88%
“…Our first finding with multimodality jICA extends our earlier MRI findings of partially dissociated structural and physiological alteration in behavioral variant frontotemporal dementia based on simply combining the statistics from structural and perfusion MRI (Shimizu et al, 2010). The observed dissociations involved substantial atrophy in absence of rCBF* reduction in some brain regions in behavioral variant frontotemporal dementia while other brain regions showed concordant levels of atrophy and rCBF* reductions.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, to identify regions of concordance and discordance between structural and physiological brain changes in neurodegenerative diseases without explicitly modeling the relationships, we developed functions to combine the statistics from different MRI modalities (Hayasaka et al, 2006). We recently applied this approach to study regional dissociations between brain atrophy and reduced rCBF in FTD, showing regionally varying reduction in rCBF despite widespread tissue atrophy (Shimizu et al, 2010). Moreover, to determine the added value of perfusion-weighted MRI beyond the value of structural MRI for the correct classification of AD, we performed cortical point-by-point tests based on logistic regressions to identify the regions where largely atrophy contributed to the classification and regions where reduced rCBF alone or in conjunction with atrophy made contributions (Tosun et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…; Shimizu et al . ). The presence of posterior cingulate hypoperfusion has recently been shown to be a sensitive early stage differential diagnostic marker in separating AD from bvFTD (Steketee et al .…”
Section: Neuroanatomical Signatures Of Ftdmentioning
confidence: 97%